2000
DOI: 10.1002/acp.774
|View full text |Cite
|
Sign up to set email alerts
|

Event‐related neural activity associated with prospective remembering

Abstract: This article reviews the ®ndings of recent work investigating the neural correlates of prospective remembering conducted within the context of the noticing search model using event-related brain potentials (ERPs). The presentation of a PM cue was associated with a phasic negativity (N320) Ð whose topography may be modulated by the nature of the cue Ð and two sustained modulations of the ERPs. The ®rst of these modulations re¯ected a parietal positivity±right frontal negativity that differentiated PM cue trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 19 publications
2
23
1
Order By: Relevance
“…Indeed, Gollwitzer and Cohen (2008) have pointed out that goal intentions and the intentions meant to fulfill them (i.e., implementation intentions) are drawing on prospective memory processes. This is also suggested by the fact that previous prospective memory research (West et al, 2000) has found the same parietal and right frontal activations that we observed in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, Gollwitzer and Cohen (2008) have pointed out that goal intentions and the intentions meant to fulfill them (i.e., implementation intentions) are drawing on prospective memory processes. This is also suggested by the fact that previous prospective memory research (West et al, 2000) has found the same parietal and right frontal activations that we observed in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous experiments that have utilised perceptual features of a physical stimulus to designate a PM cue (West et al, 2000(West et al, , 2006West and Krompinger, 2005), both the prospective positivity and N300 components were strongly elicited for the perceptual group. Consistent with studies that utilised a semantic feature of a physical stimulus to designate a PM cue Wilson et al, 2013), the N300 was substantially attenuated for the semantic group, while the prospective positivity was evident for both groups.…”
Section: Discussionsupporting
confidence: 87%
“…The N300 is also accompanied by a frontal positivity of similar onset but longer duration that distinguishes PM cues from the ongoing task (West, 2011). In a review paper, West et al (2000) described a programme of research supporting the specific involvement of the N300 in initial PM cue detection. PM cues could be distinguished from PM lures (stimuli that only partially fit the criteria for a PM cue), and the amplitude of the N300 was greater for correct responses to PM cues than for incorrect responses.…”
Section: Introductionmentioning
confidence: 97%
“…In particular, building on work using event-related brain potentials (ERPs; e.g., West et al, 2000West et al, , 2003, we explored the utility of skin conductance responses (SCRs) in elucidating the processes underlying retrieval in a prospective memory task. We report two experiments in which we measured SCRs to task stimuli in addition to measuring prospective remembering versus forgetting.…”
Section: Introductionmentioning
confidence: 99%